RELATIONSHIP BETWEEN DIET AND HYPERTENSION INCIDENCE IN EARLY ADULTHOOD AT SUNGAI BUNTU COMMUNITY HEALTH CENTER IN 2022 - Indah, Indah Handayani; Anggraini, Ani; Rotua Suriany Simamora (Rena Cipta Mandiri, 2024)
Hypertension is a condition in which the systolic blood pressure is above 140 mmHg and the diastolic blood pressure is above 90 mmHg. Early adulthood is from the age of 20 to 40 years. Early adulthood is very susceptible to hypertension because of increasing age and unhealthy lifestyles. Unhealthy lifestyles include smoking, lack of exercise, stress, consuming less nutritious foods. The research used is quantitative using Analytical Observation by using a cross sectional approach. The population in this study was the Sungai Buntu Community Health Center in 2022. The sample of this study was 97 respondents. The data collection technique is the Probability method with the Simple Random Sampling Technique. Data collection was done by distributing questionnaires. Research analysis was carried out by univariate and bivariate methods using chi square test. Based on the results of this study, there is a relationship between diet and the incidence of hypertension, p value (0.029).